Clinical applications of gonadotropin-releasing hormone analogues: a broad impact on reproductive medicine - Farrah L. Saleh, M.D; Hugh S. Taylor, M.D (Elsevier, 2023)
Gonadotropin-releasing hormone (GnRH) is central to the control of the entire hypothalamic-pituitary-gonadal axis. Manipulation of GnRH, in turn, regulates pituitary response and ovarian hormone production. Gonadotropin-releasing hormone analogues have revolutionized assisted reproductive technology and gynecologic practice. The recent advent of oral GnRH antagonists with an inherent rapid onset of action continues to transform the treatment options available for several common gynecologic conditions, including endometriosis and fibroids. Herein, we review neuroendocrine GnRH activity and discuss modulation of the reproductive axis by GnRH analogues for diverse clinical applications.